Operation Trinity - Riley, Clifford (39 clues. Cahill files, 2012)
Chronicles the first Vesper attack on Jan van Eyck's altarpiece at Ghent in the 1600s, then jumps to WWII and young Grace Cahill's desperate bid to save the masterwork from the Nazis.